Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 11 - Test - Page 1180: 15


$ y=-6x-9$

Work Step by Step

$ m=f^{,}(x)=\dfrac{d^2x}{dx^2}=2x $ Put $ x=-3$ So, $ m=f^{,}(-3)=2(-3)=-6$ The equation of the line is: $ y=mx+c \implies c= y-x $ Now, $ y=9-(-6)(-3)=-9$ So, $ y=-6x-9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.